Experimental Investigation of a 560 Watt Organic Rankine Cycle System using R134a as Working Fluid and Plat Solar Collector as Heat Source - Awaludin Martin; Nur, Muhammad (International Journal of Electrical, Energy and Power System Engineering, 2021)
New and renewable energy sources such as solar, geothermal, and waste heat are energy sources that can be used as a source of energy for Organic Rankine cycle system because the organic Rankine cycle (ORC) requires heat at low temperatures to be used as energy source. The experimental of Organic Rankine Cycle (ORC) systems with solar energy as a heat source was conduct to investigate a small-scale ORC system with R134a as a working fluid by varying the heat source at temperature 75⁰C-95⁰C. The experiment resulted a maximum efficiency, power of system is 4.30%, and 185.9 Watt, where the temperature of heat source is 95⁰C, the pressure and temperature of steam inlet turbine is 1.38 MPa and 67.9oC respectively. Solar energy as the main energy source in the ORC system can reduce energy use up to 49.9% or 4080.8 kJ where the temperature of the water as the heat source in the evaporator is 51°C.